1996
DOI: 10.1523/jneurosci.16-23-07533.1996
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Peptide of Alzheimer’s Disease Downregulates Bcl-2 and Upregulates Bax Expression in Human Neurons

Abstract: Neuronal apoptosis is a suspected cause of neurodegeneration in Alzheimer's disease (AD). Increased levels of amyloid beta peptide (Abeta) induce neuronal apoptosis in vitro and in vivo. The underlying molecular mechanism of Abeta neurotoxicity is not clear. The normal concentration of Abeta in cerebrospinal fluid is 4 nM. We treated human neuron primary cultures with 100 nM amyloid beta peptides Abeta(1-40) and Abeta(1-42) and the control reverse peptide Abeta(40-1). We find that although little neuronal apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
180
0
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(193 citation statements)
references
References 54 publications
11
180
0
2
Order By: Relevance
“…The accumulation of A␤-amyloid in brains with AD may be important in this regard because increased levels of Bax and p53 immunoreactivity have been localized within and around A␤-amyloid deposits in senile plaques (de la Monte et al, , 1998Su et al, 1997;Tortosa et al, 1998). Experimentally, A␤-amyloid has been shown to be neurotoxic or to induce proapoptosis and inhibit cell survival gene expression (Davis et al, 1999;Forloni et al, 1996;Giambarella et al, 1997;Gunn-Moore and Tavare, 1998;Ivins et al, 1999;Paradis et al, 1996;Prehn et al, 1996;Sayre et al, 1997a;Yamatsuji et al, 1996) and activate oxidative stress-related genes (Pappolla et al, 1998). Moreover, A␤-amyloid-induced cellular degeneration can be rescued or prevented by treatment with antioxidant or free-radical scavenger agents (Prehn et al, 1996).…”
Section: Figurementioning
confidence: 99%
“…The accumulation of A␤-amyloid in brains with AD may be important in this regard because increased levels of Bax and p53 immunoreactivity have been localized within and around A␤-amyloid deposits in senile plaques (de la Monte et al, , 1998Su et al, 1997;Tortosa et al, 1998). Experimentally, A␤-amyloid has been shown to be neurotoxic or to induce proapoptosis and inhibit cell survival gene expression (Davis et al, 1999;Forloni et al, 1996;Giambarella et al, 1997;Gunn-Moore and Tavare, 1998;Ivins et al, 1999;Paradis et al, 1996;Prehn et al, 1996;Sayre et al, 1997a;Yamatsuji et al, 1996) and activate oxidative stress-related genes (Pappolla et al, 1998). Moreover, A␤-amyloid-induced cellular degeneration can be rescued or prevented by treatment with antioxidant or free-radical scavenger agents (Prehn et al, 1996).…”
Section: Figurementioning
confidence: 99%
“…29 Moreover, evidence suggesting a cause-and-effect relation between increases in Bax expression and ischemia-associated neuronal cell death has come from experiments using baxÀ/À mice generated by Korsmeyer et al 30 Elevations in Bax protein and mRNA levels were described in neurons in vivo after excitotoxic lesion with the N-methyl-D-aspartate receptor agonist, quinolinic acid, 31 as well as after systemic administration of kainic acid. 32 Of potential relevance to neurodegenerative diseases, amyloidbeta peptide was reported to upregulate Bax and downregulate Bcl-2 in cultured human neurons, 33 and systemic administration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) has been shown to cause increases in Bax mRNA and protein in the substantia nigra. 34 In addition to neuronal cell death associated with ischemia and excitotoxic neurotransmitters, Bax protein levels are markedly increased in sensory and motor neurons following sciatic nerve transection, often in association with increases in Jun protein production.…”
Section: Introductionmentioning
confidence: 99%
“…2 Other studies pointed out that the expression of Bax increases during PCD, as well as under pathological conditions. 3,6,[10][11][12][13] In the present studies, we initially examined the effects of Bax overexpression on several different neuronal populations that undergo normal PCD. These include the early phase of developing retinal PCD which appears to be induced by death signaling through NGF and TGF-b, 30,31 as well as the common type of neuronal PCD that occurs in developing sensory and MNs of the spinal cord after forming synaptic connections with targets.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,10 The balance can be changed in favor of proapoptosis in several pathological conditions which cause neuronal damage. [11][12][13] It has been previously reported that overexpression of Bax induces death of cultured neurons in the absence of obvious apoptotic stimuli. 3 Therefore, the relative levels of Bax expression may in itself be important for regulating cell death in developing neuron even in the absence of extracellular proapoptotic signals.…”
Section: Introductionmentioning
confidence: 99%